Safe and Effective Chin Augmentation With the Hyaluronic Acid Injectable Filler, VYC-20L. Issue 1 (January 2021) - Beer, Kenneth; Kaufman-Janette, Joely; Bank, David; Biesman, Brian; Dayan, Steven; Kim, William; Chawla, Smita; Schumacher, Andrew
Abstract : BACKGROUND: VYC-20L is a hyaluronic acid soft tissue filler with lidocaine designed to restore facial volume. OBJECTIVE: Evaluate the safety and effectiveness of VYC-20L in patients with chin retrusion. MATERIALS AND METHODS: Adults with chin retrusion were randomized (3:1) to receive VYC-20L in the chin at study onset (treatment group) or 6 months later (control group). The primary effectiveness end point was ≥1-point improvement on the Allergan Chin Retrusion Scale (ACRS) from baseline at Month 6. Safety assessments included injection site responses (ISRs) and adverse events (AEs). RESULTS: VYC-20L was administered to 192 participants (treatment group, n = 144; control group, n = 48). At Month 6, significantly more participants had an ACRS response in the treatment versus control group (56.3% vs 27.5%; p = .0019). Effectiveness was also demonstrated by the proportion of participants with improved/much improved Global Aesthetic Improvement Scale scores and responses on the FACE-Q Satisfaction with Chin questionnaire and FACE-Q Psychological Wellbeing module. Treatment benefit remained evident at Month 12. Most common ISRs were tenderness (81.1%) and firmness (75.1%). One participant (0.5%) discontinued the study due to 2 treatment-related serious AEs of facial cellulitis and injection site inflammation, both resolved without sequelae. CONCLUSION: VYC-20L significantly improved an ACRS response and was generally safe and well tolerated. Abstract : Supplemental Digital Content is Available in the Text.